DYNAMIC PROBABILITY OF THE INDONESIAN ARCHIPELAGO UNDERWATER DEFENCE WITH SUBMARINE SONAR - Avando Bastari; Benny Sukandari; Joni Widjayanto; Dani Hutabarat (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
This paper study the determination of the number submarine defenses for Indonesian archipelago underwater defenses with probability method approach. In performing these calculations the authors perform the processing of data from various sources, both from the literature, the data from the relevant authorities in this regard Operations staff, Submarine Force with the elements in the form of operating reports, obtained through interviews and from the field. From these data processed probability calculation and the result obtained is inserted into the formula length / width of the waiting area submarine patrol positions further implemented method of calculating the probability to obtain optimal results. The result of this study is to know the total number of submarines are needed to maintain the strategic straits Indonesia as much as 13 submarines. With the percentage of each strategic submarines: 23% Makassar Strait (3 Submarines), the Lombok Strait 15.4% (2 Submarines), Strait of Halmahera 30.77% (4 Submarines), Wetar Strait 15.4% (2 Submarines), Strait Ombai 15.4% (2 Submarines). If there is a dynamic field that can easily be placed in the strait Submarines received threats in accordance with the percentage division. Suppose a threat occurs only in Hot Area I (Makassar Strait and the Strait of Lombok) then placed Submarines strength at 35.4% (5 Submarines).Keywords: Submarine, Probability Concepts, Determination of Total submarine